Value of single-center fecal calprotectin in the early diagnosis and assessment of necrotizing enterocolitis in premature infants - ZongLi, Chen; KeYong, Luo; Liang, Jiang (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the value of fecal calprotectin (FC) in the early diagnosis of necrotizing enterocolitis (NEC) in premature infants.MethodsFrom September 2021 to June 2024, 84 premature infants with NEC were selected as the NEC group, and 84 premature infants with feeding intolerance (feeding intolerance group) and 168 healthy premature infants (healthy group) were selected at the same time. ROC curves were used to analyze the value of FC in the early diagnosis and condition evaluation of NEC in premature infants, and Spearman correlations were used to analyze the relationships between FC and the occurrence and severity of NEC in premature infants.ResultsFC levels in the NEC group were greater than those in the feeding intolerance group and healthy group (P < 0.05), and there was no significant difference between the feeding intolerance group and the healthy group (P > 0.05). The FC level of premature infants with NEC III was greater than that of premature infants with NEC Ⅰ and Ⅱ, and the FC level of premature infants with NEC II was greater than that of premature infants with NEC Ⅰ (P < 0.05). ROC curve analysis revealed that the best diagnostic values of FC for premature infants with NEC and their conditions were 8.40 μg/g and 53.50 μg/g, respectively, and the AUCs were 0.651 and 0.901, respectively, with sensitivities of 42.86% and 85.71%, specificities of 89.23% and 82.61%, respectively. Spearman correlation analysis revealed that FC was positively correlated with the occurrence and severity of NEC in premature infants (rs = 0.401, 0.853; P < 0.05).ConclusionThe level of FC in premature infants with NEC is abnormally high, and FC has high clinical value for early diagnosis and condition evaluation of premature infants with NEC, which is worthy of further investigation.